Design matrix for social sustainability through architecture and vertical farming in Masjid Tanah, Malacca - Kim, Zhao Wei (2017)
Social sustainability plays an important role in forming a vibrant and culturally strong place. It emphasizes the connectivity between places and people, making the place as a bonding medium for the people. Masjid Tanah, a Malacca town is facing a problem of losing its young population whereby the place has no community hub that empowers the local and with a local market that is less integrated which caused pollution. The aim of this research is to create a design matrix for social sustainability through architecture and vertical farming in Masjid Tanah. The matrix focuses on the access and linkages; sociability; uses and activities; and comfort and image. These aspects are intended to empower the local economy activities and connect the local community. The research examines the local community and economic activities that pose opportunity and potential to the future development of Masjid Tanah. The target groups for the research are the educational institution's staff and students around the town, as well as the residing locals. A literature review of urban terminology, methods of place making, social sustainability, and application of vertical farming is done to understand the interrelationship of these three elements, which are the place, the people, and the technology. Then, a design matrix framework is formed to analyze three case studies of vertical farming facilities, which then is used to propose the design matrix for Masjid Tanah. The findings are acquired through site observation, ethnographic study, and interviews for collecting information about Masjid Tanah town center. Two design matrices are proposed, one for the urban scale and one for the standalone building scale, based on the analysis of the findings. Finally, the research proposes a viable solution by using architecture and vertical farming technology to revitalize the town in terms of social sustainability.